The Philippines electoral context and nuisance candidates. - Quintana, Michael Ray B. (2009.)
The first section of the paper discusses the political context of Philippine elections, wherein a historical narrative establishes several problems pertaining to the immaturity of Philippine democratic institutions as being a byproduct of a colonial imposition. This in turn leads to the creation of a political culture which is highly elitist and disenfranchises the vast majority of Filipinos, in terms of direct political participation. The creation then of stereotypes is a result of the Philippine legal framework operating in this patron-clientistic context, where an idealized image of an accepted figure is held by the mainstream electorate. The second section of the paper looks into how these rather unorthodox candidates come about as a result of such a context, and how they are further marginalized by the portrayal they receive in mass media and by how they are treated by their more established opponents. Another angle is also looked at, where such media treatment is also to a certain extent, beneficial to these otherwise unpopular candidates. Public perception is then held as a focal point in this analysis, as it eventually becomes the key reference point in terms of overall impact of these nuisance candidates. The third part of the research looks at how the nuisance candidates themselves perceive the public response to them, the actions of their well established opponents, and the key agencies of the government against or in favor of them, where they continue to be unruffled despite these measures and actions. The last chapter then looks at how these set of stereotypes held by the public and shared as well by both popular and unpopular candidate serves to strengthen the already existing societal bias regarding the said nuisance candidates.
Research Project (Undergraduate, Bachelor of Arts in Political Science) College of Arts and Sciences, University of the Philippines Visayas, Miagao, Iloilo. 2009.
Keywords: Elections -- Philippines -- Research